Relationships between weaning weight, maternal weaning weight, and milk production in polled Hereford cattle - J.B. Jr. Glaze; R.R. Schalles (Kansas Agricultural Experiment Station Research Reports, 1995)
Performance data from a Polled Hereford herd selected for improved feed conversion were used to calculate a variety of genetic parameters. Heritabilities were .14 for weaning wt, .18 for maternal weaning wt., and .19 for milk production. The genetic correlations were -.10 between weaning weight and maternal weaning weight and 0 between weaning weight and milk production. However, the genetic correlation between maternal weaning weight and milk was . 99, indicating they are essentially the same trait. Milk EPDs published by most breed associations are calculate d as the maternal weaning weight. Our study strongly supports this method of estimating an animal's genotype for milk production.
Keywords: Cattlemen' s Day; 1995; Kansas Agricultural Experiment Station contribution; no. 95-357-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 727; Beef; Weaning weight; Maternal weaning weight; Milk production; Heritabilities; Genetic correlations